Legends of the Atayal People on Formosa - Scheerer, Otto Johns (The Archive; The Archive Classics: Legends of the Atayal People on Formosa, 2023)
In the spring of 1930, I took advantage of a trip to Japan that was undertaken from Manila, my place of residence, to visit the Japanese island of Formosa. The purpose of this detour, for which the Notgemeinschaft der Deutschen Wissenschaft (Emergency Association of German Science) had kindly contributed the largest part of the funds, was linguistic research among the mountain people of the island. The purpose was to promote the study of native languages, in which, up until now, one most often has been content with word collections. Since the available time was too short to cover a larger part of the island, the intended research work was limited to the most northern part of the mountainous interior.